Electrochemical Preparation of Nanocatalysts and Their Application in Electrocatalysis - Zhou, Hao (International journal of analytical chemistry, 2022)
In order to solve the basic problem of high-temperature sintering of molybdenum carbide restricting the efficient construction of molybdenum carbide nanostructures and the full play of hydrogen evolution performance, this article studies the preparation of nano molybdenum carbide/boron nitrogen codoped two-dimensional carbon composite structure catalysts and the electrochemical hydrogen evolution reaction performance. Based on the self-assembly process of gelatin molecules on the surface of a two-dimensional layered boric acid crystal template, a new strategy for constructing a high-performance electrochemical hydrogen evolution reaction catalyst based on molybdenum carbide/boron nitrogen codoped two-dimensional nanocarbon composite structure (η-MoC@ BN-CSs) was established. The experimental results show that the overpotential of hydrogen evolution reaction based on molybdenum carbide/boron nitrogen codoped two-dimensional nanocarbon composite structure catalyst is 159 mV, which is slightly higher than 67 mV of commercial Pt/C catalyst, but lower than the reported literature value in the list. The Tafel slope is 68 mV·dec−1, which is slightly higher than that of the commercial Pt/C catalyst (40 mV·dec−1) and the reference value (58 mV·dec−1), but lower than those of other reported literature values in the list, indicating that the molybdenum carbide/boron nitrogen codoped two-dimensional carbon nanocomposites have excellent catalytic performance under alkaline conditions. Conclusion. This kind of two-dimensional nanocomposite structure shows platinum-like catalytic activity when used as an electrochemical hydrogen evolution catalyst in alkaline electrolyte. It has better reaction kinetics and better stability.